The efficacy of antivenom in the treatment of bites by the Papuan taipan (Oxyuranus scutellatus canni). - Trevett, A; Lalloo, D; Nwokolo, N; Naraqi, S; Kevau, I; Theakston, R; Warrell, D (1995)
A prospective series of 156 patients systemically envenomed following the bite of a Papuan taipan (Oxyuranus scutellatus canni) were studied. All patients were treated with appropriate antivenom and clinical course and outcome were compared. The proportion of patients requiring intubation was significantly smaller, and the time to resolution of neurotoxicity and discharge from hospital significantly shorter, in patients receiving antivenom no more than 4 h after the bite. No significant difference in outcome was demonstrated between patients receiving antivenom at various times after 4 h. No difference was demonstrated in the times to restoration of coagulability between the 2 groups. The only significant difference between a small number of patients given 2 vials of antivenom and patients given a single vial at the same time after envenoming was a marginally shorter duration of intubation in those who required it. The study suggests that, to achieve significant clinical benefit in Papuan taipan bite, antivenom must be given as early as possible.